Using Pseudomonas aeruginosa to Treat Soil Polluted with Gasoline - Neif, Raad; Al-Mayaly, Ithar (Iraqi Journal of Science, 2025)
Pseudomonas aeruginosa was isolated from three soils contaminated with gasoline which leak from electricity generators that used in different regions in Baghdad. The regions choices to collect the contaminated soils were Al-Dora, Al-Jadryia and Tunis quarter. The bacterial isolate is identified according to international biochemical methods and through the identification and selection the P.aeruginosa in order to use to degrade the gasoline also it was found that the optimum temperature and pH were 35°C and 9 to the P.aeruginosa, as well as using Fourier transmission infrared (FTIR) technique in order to test the ability of isolated bacteria to biodegrade the gasoline in order to use this bacteria in biodegradation for contaminated soils with gasoline. And results of using FTIR technique appended the degradation by P.aeruginosa. Results of (FTIR) technique referred to that the P.aeruginosa appeared an ability of degradation in the first day comparing with control , and some materials were appeared because of degradation such as Alcohol , where in third day the biodegradation by P.aeruginosa was very clear , also an increasing in peak area which refers to many compounds as sodium, Al-dehyd and alkanes . In fifth day, an increasing in biodegradation was observed in alkanes while in the eighth day - as in the tenth day -appeared an increasing in biodegradation.